Question #507e9

1 Answer
Sep 27, 2017

(3x+8)(x-1) =0

i.e. x= -2 2/3 or x=1

Explanation:

-3x^2-5x+8=0

3x^2+5x-8=0

The product of coefficient of first and last term is 3\times-8 = -24

So we need to find two such numbers whose sum is equal to the middle term 5and product is -24.

8 and -3 are two numbers which sum up to 5and their product is -24. Therefore we write the equation as:

3x^2 -3x +8x-8=0

3x(x -1) +8(x-1)=0

(3x+8)(x-1) =0

Therefore:
(3x+8) =0 i.e. x= -8/3 = 2 2/3
or
(x-1) =0 i.e. x=1

Answer : x= -2 2/3 or x=1